SKRINING AKTIVITAS ANTIOKSIDAN EKSTRAK METANOL LIMA BIJI TANAMAN TERHADAP DPPH (2,2-DIPHENYL-1-PICRYLHYDRAZYL) DAN PENETAPAN KADAR NUTRISI TEPUNG BIJI TERPILIH - Yeni Indra Kumalasari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Kristen Indonesia Toraja, 2017)
Antioxidant is a compound that can inhibit oxidation by reacting with reactive free radical to form reactive free radicals which was relatively stable. Phenolic compounds are a source of natural antioxidants found in plants. There are many sources of antioxidants found in fruits and vegetables. However, research on seeds are still not widely reported because so far only a few seeds discarded and few are exploited. Some seeds are thought containing antioxidant compounds are pea seeds (Pisum sativum L.), red beans (Phaseolus vulgaris L.), papaya seeds (Carica papaya L.), pumpkin seeds (Cucurbita moschata Duchesne) and avocado seeds (Persea americana Mill.). The aims of the study are to determine the seed that has the highest antioxidant activity and total phenolic content of methanol extracts from five seeds, and to determine the levels of ash content, water, carbohydrates, proteins, and fats from selected seed. Five seeds solvent extraction using methanol, followed by antioxidant activity assay against DPPH (2,2-Diphenyl-1-Picrylhydrazyl) and determination of phenolic content using Folin-Ciocalteu reagent. Once the seeds are known containing the highest antioxidant activity was processed into flour and nutritional assay performed with proximate assay which are ash content, water, carbohydrates, proteins, and fats. The assay results showed that the methanol extract of pumpkin seeds have the highest antioxidant activity of ARP value is 2.51 and total phenolic content is 1370.1 mg/mL. Nutrition content of pumpkin seed flour is 3.55% ash content (mineral), 8.97% water content, 19.51% carbohydrate, total protein 31.72%, and 36.25% total fat.